Exploring the Integration of Inquiry Based Learning into English Instruction at the Elementary School Level: A Qualitative Descriptive Study - Dina Syarifah Nasution; Karimaliana (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The integration of innovative teaching methods into early education is crucial for creating a dynamic and engaging learning environment. Among these methods, IBL stands out for its potential to develop critical thinking, creativity, and active participation among students. This qualitative descriptive research investigates integrating IBL into English instruction at the elementary school level. The study explores teachers’ perspectives on incorporating inquiry-based methods, students’ experiences, and engagement with such approaches and identifies challenges and successes in implementing IBL. Data were collected and analyzed thematically through interviews, classroom observations, and document analysis. The findings reveal that teachers view IBL positively, recognizing its potential to enhance critical thinking skills and student engagement. However, challenges such as time constraints and concerns about standardized testing were also identified. Students reported increased motivation and collaborative learning experiences through inquiry-based instruction. The study highlights the significance of IBL in promoting a deeper understanding of language concepts and fostering essential skills for 21st-century learners. Recommendations for future practice and research support further integrating inquiry-based methods into elementary English instruction.